Penerapan Metode Artikulasi pada Mata Pelajaran Fikih Kelas VIII MTs Al-Akbar Kota Sorong - Abdul Kabir Aineka; Muhammad Rusdi Rasyid (IAIN Sorong, 2028)
This research is motivated by the low learning outcomes of students of class VIII MTs Al-Akbar Sorong City on Jurisprudence subjects caused by Jurisprudence teachers in presenting subject matter which is sometimes monotonous. Teachers are more likely to use the lecture method in learning so as to make students bored. Therefore the researcher chose one of the Articulation learning methods to improve student learning outcomes. This method uses a chain message delivery system, which is from the teacher to students and is passed from one student to another student. This study aims to improve student learning outcomes in Jurisprudence subjects using Articating learning methods for students of class VIII MTs Al-Akbar Sorong City. This type of research is classroom action research (CAR). The subject was students in class VIII MTs Al-Akbar Sorong City in the odd semester of 2016/2017 academic year totaling 38 people. This research was conducted in 2 cycles, namely the first cycle and the second cycle carried out as many as 4 meetings. Data retrieval is done by using test results of learning and observation. The collected data is analyzed quantitatively and qualitatively. Quantitative data is calculated using the SPSS 16.0 formula. The results obtained after the action are given, namely: (1) the activeness of students during the learning process in class has increased, (2) in the first cycle the average score of student learning outcomes tests on Jurisprudence subjects between the first and second meetings in the first cycle is 62, 89% and 74.47% and in the second cycle, the average test score of student learning outcomes in fiqh subjects has increased ie, 80.79% and 94.34%. From the results of this study, in general, it can be concluded that an increase in student learning outcomes in the subjects of Jurisprudence VIII MTs Al-Akbar Sorong after applying the Articulation method